Translocation of Platinum Anticancer Drugs by Human Copper ATPases ATP7A and ATP7B1. (27th December 2013) - Tadini‐Buoninsegni, Francesco; Bartolommei, Gianluca; Moncelli, Maria Rosa; Inesi, Giuseppe; Galliani, Angela; Sinisi, Marilù; Losacco, Maurizio; Natile, Giovanni; Arnesano, Fabio
Abstract Cisplatin, carboplatin, and oxaliplatin are widely used anticancer drugs. Their efficacy is strongly reduced by development of cell resistance. Down‐regulation of CTR1 and up‐regulation of the Cu‐ATPases, ATP7A and ATP7B, have been associated to augmented drug resistance. To gain information on translocation of Pt drugs by human Cu‐ATPases, we performed electrical measurements on the COS‐1 cell microsomal fraction, enriched with recombinant ATP7A, ATP7B, and selected mutants, and adsorbed on a solid supported membrane. The experimental results indicate that Pt drugs activate Cu‐ATPases and undergo ATP‐dependent translocation in a fashion similar to that of Cu. We then used NMR spectroscopy and ESI‐MS to determine the binding mode of these drugs to the first N‐terminal metal‐binding domain of ATP7A (Mnk1).